(3GdOjHGL GdePgH aj eYQaI CYjGf YdeGA GdePgHs - (3EHQGgje Hf Ydj Hf eMeO, GHf aQMhf, HQgGf GdOjf GdjYeQj J (B799 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HGQF GdfSe, eHjO GdCee , HGYK GdQee , GdefRg Yf GdafGA hGdYOe s
(3BNQgG (B:s
(3bGd eDdag hcGf GdaQGZ ef JCdjag aj TgQ TYHGf , ef TghQ SfI EMOi hSJjf hSHYeGFI hGdMeO ddg hMOg s
(3GfXQ Qbe (B1048 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B52 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
Keywords: (3GdJGQjNs